Technology advancement in vehicle monitoring system for accident prevention - Chai, Neeping; Wan Azlan, Wan Zainal Abidin; Wan Hashim, Wan Ibrahim; Kismet, Hong Ping (Universiti Malaysia Sarawak (UNIMAS), 2012)
Significant development in urbanized cities causes vehicle ownership to grow with rapid rate. As a result, the saturation of vehicle in dense cities leads to insufficient transportation infrastructure, which causes an increase in road accident occurrences. The condition of vehicle and driver such as poor engine operation system, speeding, reckless driving, drowsy driving, drunken driving are the factors of accidents. Vehicle monitoring system is thus very important to be deployed as an effort for accident prevention to reduce the number of road accidents. This paper reviews the recent progress and development of technologies in vehicle monitoring system for accident prevention. Various technologies in the system include Global Positioning System (GPS), Geographical Information System (GIS), Global System for Mobile (GSM), General Packet Radio Service (GPRS), image processing, Fuzzy Logic, data fusion and so forth. The issues and challenges in vehicle monitoring system are also presented in this paper.